Design and analysis of three-to-five-phase transformer for multiphase load - Mohd Yusoff, Nor Azizah (2016)
This research is focusing on a development of a multiphase transformer, or more specifically a three-to-five-phase transformer. The development of this transformer is based on the manipulation of the phasor diagram. The two input voltage phasors are added together in order to generate the output voltage on the secondary side of the three-to-five-phase transformer. The connection is modelled and validated in finite elements methods (FEM) software prior to the fabrication process. The performance of the developed three-to-five-phase transformer is analysed experimentally using No-load test and then followed by using two types of load; static resistance (R) and inductive (L) load and finally with the dynamic load. The No-load test is performed to verify the calculated phase to phase turn ratio, which in this case is 1: 1. Thus, the amplitude of the output voltage is equal to the input voltage. For the static load test, each phase of the transformer is connected to the R load and the RL load that connected in series. Then, the analysis of the three-to-five-phase transformer with dynamic load is conducted by using a five-phase squirrel cage induction motor. The developed transformer is supplying the motor that has been coupled with electromagnetic brake. The braking power of the electromagnetic brake can be increased or decreased by varying the variable DC voltage supply. This experiment has been carried out to represent the actual load as in the industrial machineries or equipment. Therefore, the successful of static transformation design is elaborated by using the simulation and experimentation method. The simulations result is capable to generate five-phase output and the five-phase induction motor under loaded condition is used to prove the viability of the transformation system. Finally, it is expected that the development of three-to-five-phase transformer can be used for drives application and may also be further explored to be utilized in power transmission system.